Formação educacional para os direitos do cidadão em saúde : uma contribuição - Lozzo, Claudia Inês Aparecida da (2007)
This research whose subject is Citizens Right in public health was developed at EE Prof. Mercedes Paz Bueno and it investigates the students knowledge about the Single System of health having the objective of contributing for the upbringing of the young and critic adult and make him conscious of his multiply role of information while trying to increase his conscience of his controlling role and his participations in the decisions and actions how is predict in the SUS principles. This report had as an beginning point the diagnosis of what the students already know or not about the function, programs and treatment of the health public system in his city, and his knowledge about the laws that control and garantees his health as a right and duty of the State. This survey was realized with 441 adolescents from 5a. to 8a. Classes, the first test was an exposition class with several activities, using a variety of techniques with the objective of arousing the student' s interest of learning. After the educative program, was done an after test where it was concluded that there was the understanding and building of knowledge what confirms the importance of the teacher and the importance of school in the young citizen formation and the importance of putting together more and more the education and health areas because the first one is necessary to promote, protect and get back population's health. Health must be seen during the year at school in a "interdisciplinary way as a transversal continuous way, organizes by the group of teachers leading the student to relate the theory taught to his real life, what will result in his learning, changing of habits and better quality of life for his family, the community he is inserted in and for him.